2016
DOI: 10.1016/j.rboe.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Are the good functional results from arthroscopic repair of massive rotator cuff injuries maintained over the long term?

Abstract: ObjectiveTo evaluate whether the good and excellent functional results from arthroscopic repair of massive rotator cuff tears are maintained over the long term.MethodsFrom the sample of the study conducted by our group in 2006, in which we evaluated the functional results from arthroscopic repair of massive rotator cuff tears, 35 patients were reassessed, 8 years after the first evaluation. The inclusion criteria were that these patients with massive rotator cuff tears operated by means of an arthroscopic tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
2
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
3
2
0
3
Order By: Relevance
“…Few other studies reported results of arthroscopic RC repair with medium to long follow-up: Marrero et al 30 evaluated 33 tears of different sizes at a minimum follow-up of 9 years, reporting a mean UCLA score of 31.8, with 87.7% excellent and good outcomes. Similar results were also reported by Miyazaki et al 34 on 35 arthroscopic repairs of massive RC tears, which maintained good functional results (UCLA score, 31.31) and satisfaction after a minimum follow-up of 9 years. Denard et al 10 reported 78% good to excellent outcomes at a minimum 5-year follow-up after arthroscopic RC repair of massive RC tears (mean UCLA, 30.7; mean American Shoulder and Elbow Surgeons, 85.7), further suggesting that double-row repair can provide a superior UCLA score compared with single-row technique.…”
Section: Discussionsupporting
confidence: 88%
“…Few other studies reported results of arthroscopic RC repair with medium to long follow-up: Marrero et al 30 evaluated 33 tears of different sizes at a minimum follow-up of 9 years, reporting a mean UCLA score of 31.8, with 87.7% excellent and good outcomes. Similar results were also reported by Miyazaki et al 34 on 35 arthroscopic repairs of massive RC tears, which maintained good functional results (UCLA score, 31.31) and satisfaction after a minimum follow-up of 9 years. Denard et al 10 reported 78% good to excellent outcomes at a minimum 5-year follow-up after arthroscopic RC repair of massive RC tears (mean UCLA, 30.7; mean American Shoulder and Elbow Surgeons, 85.7), further suggesting that double-row repair can provide a superior UCLA score compared with single-row technique.…”
Section: Discussionsupporting
confidence: 88%
“… 1 2 The number of anchors used for lesion repair did not influence functional outcomes. In addition, it did not influence the performance or not of the total Mumford procedure and of acromioplasty, as corroborated by Miyazaki et al 21 …”
Section: Discussionsupporting
confidence: 56%
“…Observa-se na literatura poucos estudos que avaliam os escores funcionais de pacientes submetidos ao reparo videoartroscópico do MR com um seguimento pós-operatório mínimo de 10 anos. 20 21 22 23 24 25 26 …”
Section: Discussionunclassified
See 1 more Smart Citation
“…Nonoperative treatment does not reduce tear size or alter the natural history of rotator cuff disease 1 - 5 . Rotator cuff repair can result in an intact bone-tendon interface 16 , 21 , 22 , and these results can be maintained in the long term 14 , 23 - 26 . However, it remains unknown whether rotator cuff repair alters the natural history of rotator cuff disease.…”
mentioning
confidence: 99%